The people's law enforcement board of Iloilo City (1992-1998). - Taton, Rodel A.
This descriptive research seeks to discover which is the most critical factor that contibutes to the performance effectivity and efficiency of the civilian People's Law Enforcement Board (PLEB) of Iloilo City as an administrative disciplinary machinery against members of the police force from 1992-1998. The factors identified by the researcher are the following: (1)judicial capability of PLEB members, (2)requirements and procedures adopted by the PLEB, (3)types of cases presented, and (4)nature and timeliness of the administrative and logical support from the city government. The researcher took an open-ended interview with the PLEB members and a - point Likert Scale structured questionnaire was employed to measure the motivation and attitudes of the respondents., The PLEB is primarily tasked to hear and decide citizens' complaints against erring members of the police force known as the Philippine National Police. The study reveals that the most critical factor affecting the performance of the PLEB of Iloilo City is the administrative and logistical support from the city government. This kind of support according to the respondents signifies the basic requirements for PLEB to function as a disciplining body. However, the imposition of sanctions to erring members of the police force is probable only if and there is sincerity on the part of the complainants-- that is, if they have a strong belief that the law will serve the justice they are entitled to and pursue with the processes in PLEB until resolution is reached.